Influence of attentional demand and instruction on Time up and Go Test - Leite, Bruno R. (2011)
The aim of the current study was to evaluate the performance of young healthy adults on the "Timed Up and Go" (TUG) test on the dual task paradigm. Twelve young adults performed the TUG test in four conditions: a) no secondary task;b) with a task of holding a tube with both hands without defined attentional focus; c) holding the tube with internal attentional focus; and,d) holding the tube with external attentional focus. A digital chronometer was used to record the time taken to complete the tests. The movement variability of the tube was assessed by recording the kinematics of markers placed on the lateral side of the tube. Analyses of variance were used to compare the total and relative time and tube variability across conditions. More time was necessary to complete the TUG test when specific instruction about the secondary task was given, mainly when related to the movement of the tube (external focus). However, the variability of the tube was also smallest in that condition. Therefore, the addition of a secondary task (holding a tube) affects the performance of TUG only when specific instructions on the attentional focus are given in particular about external effects of the secondary task.